Prediction of the Effects of Empagliflozin on Cardiovascular and Kidney Outcomes Based on Short-Term Changes in Multiple Risk Markers - Tye, Sok Cin; de Vries, Sieta T.; Wanner, Christoph; Denig, Petra; Heerspink, Hiddo J. L. (Frontiers in Pharmacology, 2022)
Aims: The EMPA-REG OUTCOME trial demonstrated that empagliflozin reduces cardio-renal outcomes in patients with type 2 diabetes (T2D). We previously developed the parameter response efficacy (PRE) score, which translates drug effects on multiple short-term risk markers into a predicted long-term treatment effect on clinical outcomes. We assessed the accuracy of the PRE score in predicting the efficacy of empagliflozin in reducing the risk of cardiovascular and kidney outcomes. Methods: Short-term (baseline to 6-month) changes in glycated hemoglobin (HbA1c), systolic blood pressure (SBP), urinary-albumin-creatinine-ratio (UACR), hemoglobin, body weight, high-density-lipoprotein (HDL) cholesterol, low-density-lipoprotein (LDL) cholesterol, uric acid, and potassium were determined among 7020 patients with T2D and established cardiovascular disease in the EMPA-REG OUTCOME trial. The beta-coefficients, derived from a Cox proportional hazards model in a pooled database consisting of 6355 patients with T2D, were applied to the short-term risk markers in the trial to predict the empagliflozin-induced impact on cardiovasscular (composite of non-fatal myocardial infarction, non-fatal stroke, or cardiovascular death) and kidney (composite of doubling of serum creatinine or end-stage kidney disease) outcomes. Results: Empagliflozin compared to placebo reduced HbA1c (0.6%), SBP (4.2 mmHg), UACR (13.0%), body weight (2.1 kg), uric acid (20.4 µmol/L), and increased hemoglobin (6.6 g/L), LDL-cholesterol (0.1 mmol/L) and HDL-cholesterol (0.04 mmol/L) (all p<0.01). Integrating these effects in the PRE score resulted in a predicted relative risk reduction (RRR) for the cardiovascular outcome of 6.4% (95% CI 1.4-11.7), which was less than the observed 14.7% (95% CI 1.3-26.4%). For the kidney outcome, the PRE score predicted a RRR of 33.4% (95% CI 26.2-39.8); the observed RRR was 46.9% (95% CI 26.8-61.5). In a subgroup of 2811 patients with UACR >30 mg/g at baseline, the PRE score predicted 40.8% (95% CI 31.2-49.1) vs the observed 40.8% (95% CI 12.4-60.0) for the kidney outcome. Conclusions: Integrating multiple short-term risk marker changes in the PRE score underestimated the effect of empagliflozin on cardiovascular and kidney outcomes, suggesting that the currently used risk markers do not fully capture the effect of empagliflozin. In patients with increased albuminuria, the PRE score adequately predicted the effect of empagliflozin on kidney outcomes.